We Ask and Listen: A Group-Wide Retrospective Survey on Satisfaction with Digital Medication Software - Herrmann S; Giesel-Gerstmeier J; Demuth A; Fenske D (Journal of Multidisciplinary Healthcare, 2024)
Saskia Herrmann,1,2 Jana Giesel-Gerstmeier,1 Annika Demuth,1 Dominic Fenske1 1Hospital Pharmacy, Helios Kliniken Gmbh, Berlin, Berlin, Germany; 2Department of Pharmaceutical/Medicinal Chemistry, Institute of Pharmacy, Friedrich Schiller University Jena, Jena, Thuringia, GermanyCorrespondence: Dominic Fenske, Krankenhausapotheke, Helios Klinikum Erfurt, Nordhäuser Straße 74, 99089, Erfurt, Thuringia, Germany, Tel +49 361 781 71100, Fax +49 361 781 71105, Email dominic.fenske@helios-gesundheit.dePurpose: Computerized physician order entry (CPOE) and clinical decision support systems (CDSS) are used internationally since the 1980s. These systems reduce costs, enhance drug therapy safety, and improve quality of care. A few years ago, there was a growing effort to digitize the healthcare sector in Germany. Implementing such systems like CPOE-CDSS requires training for effective adoption and, more important, acceptance by the users. Potential improvements for the software and implementation process can be derived from the users’ perspective. The implementation process is globally relevant and applicable across professions due to the constant advancement of digitalization. The study assessed the implementation of medication software and overall satisfaction.Methods: In an anonymous voluntary online survey, physicians and nursing staff were asked about their satisfaction with the new CPOE-CDSS. The survey comprised single-choice queries on a Likert scale, categorizing into general information, digital medication administration, drug safety, and software introduction. In addition multiple-choice questions are mentioned. Data analysis was performed using Microsoft Office Excel 2016 and GraphPad PRISM 9.5.0.Results: Nurses and physicians’ satisfaction with the new software increased with usage hours. The software’s performance and loading times have clearly had a negative impact, which leads to a low satisfaction of only 20% among physicians and 17% among nurses. 53% of nurses find the program’s training period unsuitable for their daily use, while 57% of physicians approve the training’s scope for their professional group. Both professions agree that drug-related problems are easier to detect using CPOE-CDSS, with 76% of nurses and 75% of physicians agreeing. The study provides unbiased feedback on software implementation.Conclusion: In conclusion, digitizing healthcare requires managing change, effective training, and addressing software functionality concerns to ensure improved medication safety and streamlined processes. Interfaces, performance optimization, and training remain crucial for software acceptance and effectiveness.Keywords: computerized physician order entry, clinical decision support system, change management, feedback, electronic prescribing